Effect of magnetic ion doping on structural, electric and relaxor properties of Pb (Fe2/3W1/3) O3 multiferroic ceramics - Fraygola,Bárbara (2014)
Single-phase Pb(Fe2/3W1/3)O3 (PFW) multiferroic ceramics doped with magnetic ions were fabricated using a modified B-site precursor method. Dielectric response was investigated over a wide range of temperature and frequency. Doping did not modify the characteristic temperatures (T C, T N) and the order at ferroelectric phase transition, keeping the relaxor properties. However, the leakage current and resistivity of PFW have been improved with the substitutions: 1 mol% MnO2 addition caused a significant increase in the electric resistivity of PFW ceramics, around 7 orders of magnitude.